Local analgesia for the relief of pain in children undergoing venipuncture and intravenous cannulation: a systematic review and network meta-analysis - Liping Zhao; Ping Qi; Xue Wang; Xiaolei Su; Limei Liao (BMC Anesthesiology)
Abstract Background Venipuncture and intravenous cannulation are common procedures in hospitals that often cause pain, particularly in children. Despite the availability of various local analgesia methods to alleviate needle-associated pain, the most effective approach remains unknown. The objective of this study is to compare and rank the efficacy of different local analgesia methods in reducing pain in children undergoing venipuncture and intravenous cannulation. Method Six databases including PubMed, Embase, CINAHL, Scopus, Web of Science, and the Cochrane Library were searched from January 1,1990 to December 1,2024. The primary outcome is the self-reported pain. We assessed the certainty of the body of evidence from the NMA for the primary outcome based on CINeMA. Result 40 RCTs consisting of 4481 children and 9 local analgesia methods were included in the analysis. Results showed that vapocoolant spray was no more effective than placebo or routine care in reducing needle-associated pain in children. Other interventions including EMLA cream, lidocaine cream, lidocaine iontophoresis, amethocaine, needle-free lidocaine injection system, EMLA patch, lidocaine/tetracaine heating patch and Buzzy produced greater pain reduction in children compared to placebo and routine care. Amethocaine was the most effective local analgesia method with the probability of 57.6% being the best, followed by Buzzy and lidocaine iontophoresis with the probability of 17.0% and 8.4%, respectively. Conclusion Most local analgesia methods were effective in relieving pain in children undergoing venipuncture and intravenous cannulation except vapocoolant spray which did not show greater pain reduction than placebo or routine care. Amethocaine, Buzzy and lidocaine iontophoresis are the top 3 local analgesia methods to relieve pain in children undergoing venipuncture and intravenous cannulation. However, due to the limited number of direct comparisons, interpretation of some results should be made with caution.